Effects of low temperature on in vivo and in vitro protein synthesis in Escherichia coli and Pseudomonas fluorescens. - Broeze, R J (1978)
The effects of temperature on protein synthesis by Escherichia coli, a mesophile, and Pseudomonas fluorescens, a psychotroph, were investigated by using whole-cell and cell extract preparations. After shifts to 5 degrees C, protein was synthesized at a slowly decreasing rate for 1 h by both organisms, after which P. fluorescens synthesized protein at a new rate corresponding to its 5 degrees growth rate, in contrast to E. coli which did not synthesize protein at a measurable rate. In vitro protein-synthesizing systems using MS-2 RNA, endogenous mRNA, and purified polysomes were utilized to investigate initiation of translation at 5 degrees C. In these systems, P. fluorescens cell extracts synthesized protein at linear rates for up to 2 h at 5 degrees C, whereas E. coli cell extracts synthesized protein for only 25 min at 5 degrees C. The rates of polypeptide elongation, as tested by the incorporation of phenylalanine into polyphenylalanine by cell extract protein-synthesizing systems from both organisms, were identical over the range of 25 to 0 degrees C. The polysome profiles of E. coli whole cells shifted from 37 to 5 degrees C showed accumulation of 70S ribosomal particles and ribosomal subunits at the expense of polysomes. Similar experiements done with P. fluorescens resulted in polysome reformation at 5 degrees C. In vitro experiments demonstrated that the 70S ribosomal particles, which accumulated in E. coli at 5 degrees C, were capable of synthesizing protein in vitro in the absence of added mRNA. These in vivo and in vitro results suggest that incubation of E. coli at subminimal temperatures results in a block in initiation of translation causing polysomal runoff and the accumulation of 70S particles, some of which are 70S monosomes.